SAFETY ASPECTS OF USING DROTAVERINE IN OBSTETRIC PATIENTS - E. M. Dzhobava (Акушерство, гинекология и репродукция)
Summary Safety of pharmacotherapy during pregnancy is of paramount importance for the woman and the fetus. There is an increasing number of pediatric diseases with unclear or presumably genetic etiology (autism, mental illness, oncology, obesity, diabetes, etc.). In this respect, more attention is being paid to the epigenetic or fetal programming, and the safety of pharmacotherapy during the gestation period and lactation, as well as 3-9 months before conception (periconception period).